2017
DOI: 10.1038/srep45274
|View full text |Cite
|
Sign up to set email alerts
|

Milk Fat Globule Membrane Supplementation in Formula Modulates the Neonatal Gut Microbiome and Normalizes Intestinal Development

Abstract: Breast milk has many beneficial properties and unusual characteristics including a unique fat component, termed milk fat globule membrane (MFGM). While breast milk yields important developmental benefits, there are situations where it is unavailable resulting in a need for formula feeding. Most formulas do not contain MFGM, but derive their lipids from vegetable sources, which differ greatly in size and composition. Here we tested the effects of MFGM supplementation on intestinal development and the microbiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
2
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(125 citation statements)
references
References 71 publications
6
108
2
2
Order By: Relevance
“…Previous studies have indicated that MFGM significantly impacts on the gut microbiota (Bhinder et al., ; Le Huerou‐Luron et al., ; Thompson et al., ). In this study, MFGM significantly affected relative abundance levels of different bacteria, with the addition of the prebiotic blend further enhancing this impact.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have indicated that MFGM significantly impacts on the gut microbiota (Bhinder et al., ; Le Huerou‐Luron et al., ; Thompson et al., ). In this study, MFGM significantly affected relative abundance levels of different bacteria, with the addition of the prebiotic blend further enhancing this impact.…”
Section: Discussionmentioning
confidence: 98%
“…MFGM has also been shown to enhance sleep quality, which was related to changes in gut bacteria, and it also modulated the impact of stress on sleep (Thompson et al, 2016). MFGM supplementation has also been associated with antipyretic effects, as it decreased the incidence of middle ear infections (Timby et al, 2014) and is also associated with changes in the oral microbiota composition (Timby et al, 2014) and gastrointestinal development (Bhinder et al, 2017;Demmelmair, Prell, Timby, & Lonnerdal, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in stool consistency of both the SBS and SBS+MFGM groups were in line with the changes in body weight, with no statistical difference detected between the 2 groups. Bhinder et al found the addition of MFGM in formula resulted in increased villus length in jejunum and ileum using a pup‐in‐a‐cup model with the most significant changes in the higher dosage group, but they did not find differences in body weight among the groups . The impact of MFGM on epithelial cell proliferation and body weight might be influenced by different factors, including age, dosage, and model.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Perez et al demonstrated that breast milk contains mononuclear cells carrying bacterial DNA, which the infant uses to train the immune system to recognize these foreign DNA fragments and thus to respond appropriately to microbial challenge . Finally, breast milk contains a fat component called milk fat globule membrane, which is reported to promote tight junction architecture and bactericidal activity and also increase goblet cell numbers …”
Section: Early Life Events and Jia Riskmentioning
confidence: 99%